Effect of bonding conditions on the bonding strength in an aluminum bonding using ultrasonic vibrations and high-frequency induction heating in an atmosphere. Issue 8 (3rd August 2018) - Osada, Tomoji; Sonoya, Keiji; Abe, Takeyuki; Nakamura, Masanobu; Goto, Shuko; Otagiri, Saki
ABSTRACT: The needs of aluminium joints have grown in recent years. However, as aluminium forms strong oxide layers on the surface in an atmosphere, joining of these materials is difficult. This is why we conceived a new atmosphere solid-phase bonding method that uses high-frequency induction heating and ultrasonic vibration. The effects of ultrasonic vibration and bonding conditions on this new bonding method were investigated. As a result, we were able to confirm the efficacy of ultrasonic waves on bonding. The bonding mechanism of new bonding method was also clear.